2016
DOI: 10.2147/ott.s113417
|View full text |Cite
|
Sign up to set email alerts
|

Influence of <em>MDM2</em> polymorphisms on squamous cell carcinoma susceptibility: a meta-analysis

Abstract: PurposeControversial associations between single-nucleotide polymorphisms (rs2279744, rs937283, rs3730485) of the MDM2 gene and the etiology of squamous cell carcinomas (SCCs) have been reported. This merits further comprehensive assessment.Materials and methodsWe systematically reviewed the available data and conducted an updated meta-analysis to evaluate the genetic effect of MDM2 polymorphisms in SCC susceptibility, using Stata/SE 12.0 software.ResultsAfter screening, 7,987 SCC cases and 12,954 controls fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…The results of prediction intervals are wide, suggesting that future research may demonstrate benefit, disadvantage, or not demonstrate any statistically significant difference. [25] Similar to our analysis, some meta-analysis demonstrated that MDM2 rs2279744 is associated with squamous cell carcinoma, [26] colorectal cancer, [27] endometrial cancer, [28] and hepatocellular carcinoma. [29] But 2 meta-analyses indicated that MDM2 rs2279744 polymorphism cannot be considered as genetic risk factors for osteosarcoma, [30] and prostate cancer.…”
Section: Discussionsupporting
confidence: 83%
“…The results of prediction intervals are wide, suggesting that future research may demonstrate benefit, disadvantage, or not demonstrate any statistically significant difference. [25] Similar to our analysis, some meta-analysis demonstrated that MDM2 rs2279744 is associated with squamous cell carcinoma, [26] colorectal cancer, [27] endometrial cancer, [28] and hepatocellular carcinoma. [29] But 2 meta-analyses indicated that MDM2 rs2279744 polymorphism cannot be considered as genetic risk factors for osteosarcoma, [30] and prostate cancer.…”
Section: Discussionsupporting
confidence: 83%
“…After careful examination and assessment, three publications were excluded for the following reasons: one had duplicate data with the previous research 20 and other two were irrelevant with cancer risk. 21 , 22 All studies were in agreement with HWE, except for an article by Jin et al 11 We included this article for the further study because genotype distribution of the TP53 Arg72 Pro polymorphism was in accordance with HWE in the same study. 11 Of these 11 publications, two publications involved two cancer types 14 , 23 and one publication involved four cancer types.…”
Section: Resultsmentioning
confidence: 99%
“…A latest meta-analysis conducted by Yu et al found that there was no significant difference between del1518 polymorphism and overall squamous cell carcinoma susceptibility with a total of 309 cases and 1,000 controls from three studies, results of which is consistent with the current study. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Squamous cell carcinoma (SCC) is the most common histological type of several clinical cancers, such as head and neck cancer, esophageal cancer, skin cancer, lung cancer, and cervical cancer [ 8 , 9 ]. The exact pathogenesis of SCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Living habits (e.g., smoking, drinking), viral infection [e.g., human papillomavirus (HPV)], immune system, and polymorphic variants with many genes may be related to the risk of different SCC diseases [ 10 12 ]. Previously, we conducted an updated meta-analysis to explore the impact of MDM2 (MDM2 Proto-Oncogene) polymorphisms on SCC susceptibility and found that the GG genotype of MDM2 rs2279744 polymorphism may be associated with an increased risk of esophageal SCC in Asian populations [ 8 ].…”
Section: Introductionmentioning
confidence: 99%